Investigating the psychophysiological response to grade one muscular injury in professional Australian football athletes - Rist, B.; Pearce, A. J.; Clarke, A. C. (International Journal of Exercise Science, 2022)
The purpose of this study was to examine Australian Football athletes` responses to a grade one muscular injury from a psychophysiological perspective to understand the strength of the association between stress, optimism, and cortisol. Forty-five players listed with one professional Australian Football club volunteered for this study. Inclusion criteria consisted of sustaining a muscular injury during the course of the season with four-weeks predicted recovery time (as diagnosed by club medical staff, n=9). The control group were age, position, and career history matched players from the same sample. Players were also matched for their personality (10-item Big Five Personality Inventory) and fluid intelligence (Raven`s Standard Progressive Matrices). Injured players and matched controls completed perceived stress and optimism measures (paper-based questions) as well as salivary cortisol testing once per week for four weeks. Significant increases in cortisol (p=0.015) and perceived stress (p<0.001) were observed in injured players, along with a reduction in optimism (p<0.001) returning by week 4. A significant positive correlation was found between perceived stress and cortisol (r= 0.426), and significant negative correlations observed between optimism and cortisol r= -0.257 and perceived stress r= -0.391. This study showed that athletes were significantly stressed and less optimistic during the first two-weeks of recovery compared to matched controls. While not statistically significant, large effects observed in cortisol and stress in the week prior to returning to competition in the injured group suggest these results demonstrate that a multi-modality approach can improve understanding of psychophysiological stress following a grade one muscular injury in Australian Football athletes.